1983
DOI: 10.1111/j.1399-3054.1983.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ferric reducing activity in roots of Fe‐deficient Phaseolus vulgaris

Abstract: Iron‐deficient bean plants (Phaseolus vulgaris L. cv. Prélude) exhibited a ferric reducing activity in the roots, with kinetics characteristic for matrix‐bound enzymes: the reaction rate was proportional to substrate (Fe‐EDTA) concentration until 100 μM, and at higher concentrations it leveled off to a maximum; the Lineweaver‐Burk plot yielded a non‐linear relationship between rate −1 and substrate −1. The Arrhenius plot yielded apparent activation energies which were dependent on substrate concentration. No e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(100 citation statements)
references
References 23 publications
6
94
0
Order By: Relevance
“…These authors suggested that an "enzymic reduction of ferric ion on the plasmalemma of cortical cells of roots" was a key facet of iron assimilation by iron-deficient peanut plants [32]. Bienfait and colleagues [31,33], studying bean plants, reached similar conclusions concerning the involvement of an Fe3+-reducing enzyme in the cortex or epidermis cell plasmalemmas. In addition, data indicating the use of cytosolic NADPH as the electron source for Fe3+ reduction were also presented [33].…”
Section: Plant Iron Assimilation Modelssupporting
confidence: 51%
See 1 more Smart Citation
“…These authors suggested that an "enzymic reduction of ferric ion on the plasmalemma of cortical cells of roots" was a key facet of iron assimilation by iron-deficient peanut plants [32]. Bienfait and colleagues [31,33], studying bean plants, reached similar conclusions concerning the involvement of an Fe3+-reducing enzyme in the cortex or epidermis cell plasmalemmas. In addition, data indicating the use of cytosolic NADPH as the electron source for Fe3+ reduction were also presented [33].…”
Section: Plant Iron Assimilation Modelssupporting
confidence: 51%
“…The demonstration of Fe3+ reduction at the root surface [29,31] resulted in the proposal that a 'ferric ion reductase' is an intimate component of iron assimilation in plants.…”
Section: Plant Iron Assimilation Modelsmentioning
confidence: 99%
“…5). A broad range ofhigh Fe3" reducing ability, extending into the acid pH range, has been demonstrated for peanut roots (15) and bean roots (1). Reduction of rhizosphere pH is common under conditions of Fe deficiency for most nongraminaceous plant species (16).…”
Section: Ph Responsementioning
confidence: 99%
“…Since EDTA and BPDS complexes are membrane impermeable (Anderson and Morel 1980;1982;Price et al unpubl. ) (Bienfait et al 1983;Bienfait 1987), the ferric reductase lacks substrate specificity, as cells reduced Fe(III) bound to a variety of organic ligands (Table 4). Indeed, T. oceanica was able to reduce Fe bound to the fungal siderophore DFB at fast rates.…”
Section: Reduction Of Fe(iii) Bound To Dtpa and Dfb-mentioning
confidence: 99%